GUIDELINES FOR THE DIAGNOSIS AND MANAGEMENT OF DIABETIC RETINOPATHY AND DIABETIC MACULAR EDEMA IN INDONESIA - Harley, Ohisa; Hertanto, Martin; Sembiring, Sindy Boru; Yustiarini, Ima; Susilo, Teguh; Dharma, Andhika Guna; Sjahreza, Emil; Firmansyah, M; Iskandar, Erwin; Agustiawan, Referano; Andayani, Ari; Dewi, Nadia Artha; Andayani, Gitalisa; Djatikusumo, Ari; Elvioza, Elvioza; Ichsan, Andi M; Kartasasmita, Arief S (Indonesian Vitreoretinal Society, 2024)
Diabetic retinopathy (DR) and diabetic macular edema (DME) are among the microvascular complications in individuals with diabetes mellitus (DM) that can lead to blindness if not diagnosed early and managed appropriately. Both disorders can be diagnosed and treated using a variety of techniques. Treatment modalities include laser photocoagulation therapy, vitrectomy surgery, intraocular steroid injections, and anti-vascular endothelial growth factor (anti-VEGF) injections. These methods can help avoid blindness when used in conjunction with metabolic control. These recommendations were created with the use of evidence-based medicine principles to help medical professionals—particularly ophthalmologists—identify and treat cases of DR and DME.The primary objective is to provide consensus recommendations and hopefully reduce the incidence of blindness caused by DR and DME in Indonesia.